The Optimal Acquisition of Automation to Enhance the Productivity of Labor - Gaimon, Cheryl (Management Science, 1985)
Decisions concerning the mix of automation and labor employed by an organization are embedded in the long-term strategic plan since the composition of productive capacity impacts on an organization's ability to survive and compete. In this paper, the optimal mix of automation and labor is identified for automation which acts to enhance the productivity of an organization's workforce. The incentives considered for acquiring automation are increasing the level of output, reducing the high cost of labor, and compensating for a limited supply of labor. Factors explicitly examined by the model include the future long-term goal level of output, costs associated with maintaining the workforce (wages) and automation, and costs associated with changing the levels of workforce and automation. Since the formulation is dynamic so that all exogenous and decision variables may be expressed as functions of time, the effects of technological improvement, increasing wage rates, changing labor supply, and diminishing returns as additional automation is acquired are considered.